REALIZATION OF DOCTORAL TRAINING PROGRAMS BASED ON THE FEDERAL LAW «ON EDUCATION IN THE RUSSIAN FEDERATION» - Irina A. Mosicheva; Evgenia V. Karavaeva; Vadim L. Petrov (Высшее образование в России)
The authors dwell upon the main aspects of the development of doctoral training programs in Russia. Major trends of these programs are defined by the new federal law «On Education in the Russian Federation». The new generation of documents on the implementation of doctoral programs will ensure the conditions for high-quality preparation of scientific and pedagogical staff.